2018
DOI: 10.1177/2515690x18770631
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review on the Concept of Avapeedaka Snehapana, a Special Mode of Lipid Administration

Abstract: Avapeedaka Snehapana is a unique and special method of internal administration of Sneha dravya (unctuous medicine) mentioned in the classical ayurveda texts. It is mainly indicated in mutravegarodha janya vikara (diseases due to the suppression of urge of micturition). Because of the lack of adequate review and analysis, this method of administration of snehapana (internal administration of lipid) is losing its significance from the practices and the concept remains unexplored. The reasons for not being practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…Significant reduction in Blood urea & insignificant level of Serum creatinine in the present study shows the good normal excretory and protective role of incremental oleation over kidney [26]. Protective role of lipids consisting of polyunsaturated fatty acids for kidney in non-diabetic patients (i.e., Healthy) is also supported by Aguila MB et al [27] Yuzbashian E et al [28] based on its effects to decrease glomerulosclerosis, glomerular magnification, and glomeruli loss.…”
Section: Effect On Rftsupporting
confidence: 68%
“…Significant reduction in Blood urea & insignificant level of Serum creatinine in the present study shows the good normal excretory and protective role of incremental oleation over kidney [26]. Protective role of lipids consisting of polyunsaturated fatty acids for kidney in non-diabetic patients (i.e., Healthy) is also supported by Aguila MB et al [27] Yuzbashian E et al [28] based on its effects to decrease glomerulosclerosis, glomerular magnification, and glomeruli loss.…”
Section: Effect On Rftsupporting
confidence: 68%
“…It reverts the normalcy of Annavaha Strotas by improving appetite. 25 Panchtikta Kshir Vasti (medicated clarified butter enema with Panchagavya) is recommended for Pitta predominant and degenerative conditions due to its Pitta pacification properties, Kledahara (factor responsible for minimizing moisture), Balya (creating power), and Rasayan (rejuvenation) properties. 26 In clinical practice, it has significant results in Amlapittta Daha (hyperacidity), bone or bone marrow-based diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trial with Maha pancha gavye ghrita showed that there was significant increase in serum sodium and serum calcium levels and decrease in serum potassium levels. 8 Hence these drugs may bring about Shodhana to some extent and maintain the electrolyte balance thus bringing about equilibrium and maintaining a high epileptic threshold 9 Shodhana which includes Vamana, Virechana induces changes in the serum electrolyte levels. It has been found in previous studies that Vamana and Virechana cause these changes in the serum electrolyte levels though it is insignificant 10 .…”
Section: Mode Of Actionmentioning
confidence: 99%